Summer Grazing of Steers in Western Kansas - Sartwelle III, James D.; Jones, Rodney; O'Brien, Daniel M. (My University, 1995)
This publication is a guide to budget estimate costs and returns for a season-long and an early-intensive grazing system in Western, KS.
MF1007_1995-10
Keywords: MF1007; Economics; Livestock; MF